Positively charged microparticles in plasma - Chibisov, D.V.; Chibisov, O.D.; Zhernovnykova, O.A.; Deynychenko, G.V.; Masych, V.V. (Problems of Atomic Science and Technology, 2023)
The processes of recharging and changing the temperature of a positively charged microparticle (MP) introduced into plasma are considered. It is assumed that the MP is charged to a positive charge outside the plasma, and then enters the plasma due to the accelerating field. For various values of plasma density and temperature, a numerical solution of the energy and current balance equations of a MP is obtained. The equation that determines the evapora-tion of particles is solved numerically. The time dependence of the radius of a MP during evaporation has been ob-tained. Розглянуто процеси перезарядки та зміни температури позитивно зарядженої мікрочастинки (МЧ), введеної в плазму. Передбачається, що МЧ заряджається до позитивного заряду поза плазмою, а потім потрапляє в плазму в результаті прискорювального поля. Для різних значень густини та температури плазми отримано чисельний розв’язок рівнянь балансу енергії та струму МЧ. Чисельно розв’язано рівняння, яке визначає можливість випаровування таких частинок. Отримано часову залежність радіусу МЧ при випаровуванні.